2021
DOI: 10.1182/bloodadvances.2021004575
|View full text |Cite
|
Sign up to set email alerts
|

CRP and ferritin in addition to the EASIX score predict CAR-T–related toxicity

Abstract: The Endothelial Activation and Stress Index (EASIX) score, defined as [(creatinine × lactate dehydrogenase [LDH])/platelets], is a marker of endothelial activation that has been validated in the allogeneic hematopoietic stem cell transplant setting. Endothelial activation is one of the mechanisms driving immune-mediated toxicities in patients treated with chimeric antigen receptor-T (CAR-T)-cell therapy. This study’s objective was to evaluate the association between EASIX and other laboratory parameters collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 28 publications
4
58
1
1
Order By: Relevance
“…While tumor burden is associated with risk of severe CRS in NHL, several groups are investigating the use of baseline, pre – lymphodepletion laboratory parameters as risk predictors of CRS and ICANS. More recently, investigators have evaluated the use of the Endothelial Activation and Stress Index (EASIX) [lactate dehydrogenase (U/L(x creatinine (mg/dL)/platelet count (10 9 cells/L)] ( 40 ), with either use of CRP concentration instead of creatinine (modified EASIX, mEASIX) ( 41 ) or in combination with ferritin and CRP concentrations (EASIX-FC) ( 42 ). These modifications of the EASIX score can predict the risk of CRS and) ICANS and mEASIX can also predict disease response ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…While tumor burden is associated with risk of severe CRS in NHL, several groups are investigating the use of baseline, pre – lymphodepletion laboratory parameters as risk predictors of CRS and ICANS. More recently, investigators have evaluated the use of the Endothelial Activation and Stress Index (EASIX) [lactate dehydrogenase (U/L(x creatinine (mg/dL)/platelet count (10 9 cells/L)] ( 40 ), with either use of CRP concentration instead of creatinine (modified EASIX, mEASIX) ( 41 ) or in combination with ferritin and CRP concentrations (EASIX-FC) ( 42 ). These modifications of the EASIX score can predict the risk of CRS and) ICANS and mEASIX can also predict disease response ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…While some factors have already been identified for their correlation with prognosis, the prognostic factors for response to CAR-T-cell therapy are a matter of ongoing research [ 12 , 13 , 14 ]. Among them, a lower LDH level before lymphodepleting therapy preceding CAR-T-cell infusion was associated with superior progression-free survival [ 12 , 13 ], while the achievement of remission within the first three months after CAR-T-cell therapy was shown to be associated with a durable response [ 5 , 17 , 19 ]. Other parameters, e.g., whether distinct lymphoma subtypes respond better to CAR-T-cell therapy than others, currently remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the rapidly increasing number of clinical reports, uncertainty remains regarding the factors that impact clinical outcomes after CAR-T-cell treatment [ 4 , 5 , 6 , 12 , 13 , 14 , 15 ]. In particular, it remains unclear whether distinct lymphoma subtypes may differ in their response to CAR-T-cell treatment [ 1 , 6 , 7 , 16 , 17 , 18 ]. For example, a recent report suggested that patients with a history of follicular lymphoma had a better progression-free course than patients with DLBCL [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial cell damage and capillary leak are clinical hallmarks of CRS ( Figure 1 ). The endothelial activation and stress index (EASIX) is defined as [(creatinine level × lactate dehydrogenase (LDH)) level/peripheral blood platelet count], and this marker of endothelial activation has been validated in the CAR-T cell therapy setting [ 53 ]. This study included patients who received treatment with CAR-T cells, and the authors investigated the association between EASIX and the immune effector cell-associated neurotoxicity syndrome (ICANS) in a group of 171 patients treated with axicabtagene ciloleucel (axi-cel) for large B-cell lymphoma.…”
Section: Pathophysiology and Biomarkersmentioning
confidence: 99%
“…As stated above the EASIX index has also been investigated as a possible biomarker in combination with CRP and ferritin [ 53 ]. This index could identify three different patient subsets regarding development of CRS Grades 2–4 with 74%, 51%, and 29% cumulative incidences.…”
Section: Pathophysiology and Biomarkersmentioning
confidence: 99%